2014
DOI: 10.5539/ijbm.v9n6p161
|View full text |Cite
|
Sign up to set email alerts
|

Internet financial Reporting in Malawi

Abstract: The dawn of Internet has resulting in the evolution of financial reporting from the conventional design of the printed annual report to the contemporary Internet Financial Reporting (IFR). Due to its growth, IFR has attracted the interest of researchers. However despite the fact that much research have been carried out, the understanding of the level of IFR is still vague. The study was an evaluation of the level of IFR focusing on a developing country, Malawi. The study used content analysis methodology and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Although the signaling theory states a positive and direct relationship between performance and disclosure, it will be interesting to investigate the effect of disclosure through OFD on the performance of Islamic banks, so as to prevent the wrong indication of the strengths of such banks. Moreover, as its growth and despite the number of researchers interested in OFD as a tool for voluntary disclosure, it remains vague in the literature (Lipunga, 2014) especially with regard to Islamic banks. Therefore, this research paper aims to investigate the relationship between OFD and the performance of Islamic banks in the Gulf Cooperation Council (GCC) countries.…”
Section: Introductionmentioning
confidence: 99%
“…Although the signaling theory states a positive and direct relationship between performance and disclosure, it will be interesting to investigate the effect of disclosure through OFD on the performance of Islamic banks, so as to prevent the wrong indication of the strengths of such banks. Moreover, as its growth and despite the number of researchers interested in OFD as a tool for voluntary disclosure, it remains vague in the literature (Lipunga, 2014) especially with regard to Islamic banks. Therefore, this research paper aims to investigate the relationship between OFD and the performance of Islamic banks in the Gulf Cooperation Council (GCC) countries.…”
Section: Introductionmentioning
confidence: 99%
“…A disclosure index can be scored in two ways: weighted and unweighted. Previous studies on corporate disclosure have commonly used the unweighted approach (Aly et al, 2010;Lipunga, 2014;Masum et al, 2021). Proponents of this approach argue that its superiority derives from the fact that it avoids the issue of subjective bias by giving equal importance to all items.…”
Section: Measurement Of Digital Reporting Using a Disclosure Indexmentioning
confidence: 99%
“…Otherwise, the Internet Financial Reporting literature review suggested that it is a global activity. Studies suggest that many businesses rely on the Internet as one of the most important platforms for communication of financial information in many countries (Homayoun et al, 2011;Lipunga, 2014;Shukla & Gekara, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%